EXECUTING GOOGLE CLASSROOM IN TEACHING READING COMPREHENSION DURING PANDEMIC - Rachmanita; Kiki Rizki Amelia; Dita Septina Kharisma Putri (Language and Education Journal, 2022)
The objective of the study was to find out whether or not there was significant difference in reading skill between the students who were taught by using Google Classroom and that of those who were not. The method used in this study was quasi experimental method. The sample of this study was 82 students which divided into two groups, namely experimental group (VIII 2) and control group (VIII 5), each of them consisted of 41 students. To collect the data, the written test of reading skill was used in the form multiple-choice was administred. T-test was used to analyze the data. The result of independent t-test was the significant level p<0.05 with df 80, the critical value of t-table = 1.990. Since the value of t-obtained (3.179) was higher than the critical value t-table (1.990), Ho was rejected and Ha was accepted. It meant that there was a significant difference in reading skill between students who were taught by using Google Classroom and that of those who were not.